Intersections between design thinkings and teacher training (Revista Brasileira de Contabilidade e Gestão, 2017)
Innovation is an integrated element to contemporary society with new methodologies in pedagogical doing. The training of the teacher expands to an integral vision of the man that promoting new methodologies for the teaching with intersections of diverse tools. These methodological innovations are part of a new educational scenario, where the student is more participatory and autonomous in his thinking. This causes the teacher to look for a new pedagogical practice, inserting in this planning and problamticas that allow the student to motivate to learn. This makes the classroom become a space of interaction and problematizations that has as a background the tools of desinger thinking. This is used to prepare classes and also to provide new ways of teaching students of this knowledge society. Thus, the objective in this article is to map the intersections between design thinking and teacher training. A systematic search was carried out followed by a bibliometric analysis in the Scopus database. As a result, it was identified that the research emerges in the field of Socio Sciences intersecting the discussions in the Engineering area; Computer science; Environmental science; Arts and Humanities; Business, Management and Accounting; Decision Science and Medicine and congregates um novo olhar ao fazer pegagócio trazendo então uma discussão that transcends to cartezianos models of ensiling on aprendizagem was conceived em a passive process.
Keywords: design thinking; teacher; teaching